Empirically Determined Auroral Electron Events at Mars—MAVEN Observations. Issue 6 (26th March 2022) - Xu, Shaosui; Mitchell, David L.; McFadden, James P.; Schneider, Nicholas M.; Milby, Zachariah; Jain, Sonal; Weber, Tristan; Brain, David A.; DiBraccio, Gina A.; Halekas, Jasper; Ruhunusiri, Suranga; Mazelle, Christian; et al.
Abstract: Discrete aurorae have been observed at magnetized planets such as Earth and Jupiter, triggered by accelerated electrons. Similar aurorae have also been observed at Mars with only localized strong crustal magnetisms. However, our understanding of this phenomenon at Mars is still limited. In particular, direct and quantitative comparisons of the auroral and its source electron events are lacking as these two types of observations are usually made at different times and/or locations. In this study, we establish empirical criteria to select electron events ("auroral electrons") that could trigger detectable auroral emissions with Mars Atmosphere and Volatile EvolutioN measurements, thereby enabling a direct statistical comparison. We find auroral electrons share similar statistical characteristics to those previously reported for discrete auroral events. This study bridges the gap between electron observations and auroral detections and enables collaborations across different Mars missions, as well as comparative planetary studies of discrete aurora. Plain Language Summary: Aurorae have been observed in the polar regions at magnetized planets such as Earth and Jupiter, triggered by accelerated electrons. Similarly, localized auroral emissions have also been reported at Mars with no global dipole field but localized strong crustal magnetisms. However, our understanding of aurorae at Mars is still very limited in terms of their characteristics and the source electrons. In particular, direct and quantitative comparisons of the auroral and electron events are lacking as these two types of observations are usually made at different times and/or locations because of the limitation of single‐spacecraft observations. This study establishes empirical criteria to select auroral electrons and statistically compare these two types of observations. This study bridges the gap between the electron observations and auroral detections and enables collaborations across different Mars missions, as well as studies of auroral phenomena at different planets. Key Points: We establish empirical criteria to select electron events that could trigger detectable auroral observations We find similar statistical behaviors in selected electron events as discrete auroral events and explore the cause of statistical trends This study bridges the gap of these two types of observations and motivates collaborations across different Mars missions